2010
DOI: 10.1213/ane.0b013e3181e30b9f
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Efficacy of Subarachnoid Morphine in Comparison with Ultrasound-Guided Transversus Abdominis Plane Block After Cesarean Delivery

Abstract: As part of a multimodal analgesic regimen, subarachnoid morphine provided superior analgesia when compared with ultrasound-guided transversus abdominis plane block after cesarean delivery, yet at the cost of increased side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 23 publications
3
126
3
5
Order By: Relevance
“…27,28 After TAP block, differences in nausea and vomiting and pruritus were controversial in the literature, though most publications describe a higher incidence in the control groups for nausea and vomiting. 1,12,[14][15][16] Similarly, in our study, more patients in the control group had nausea and vomiting in the first 24 postoperative hours, though the difference was not statistically…”
Section: Resultscontrasting
confidence: 49%
See 2 more Smart Citations
“…27,28 After TAP block, differences in nausea and vomiting and pruritus were controversial in the literature, though most publications describe a higher incidence in the control groups for nausea and vomiting. 1,12,[14][15][16] Similarly, in our study, more patients in the control group had nausea and vomiting in the first 24 postoperative hours, though the difference was not statistically…”
Section: Resultscontrasting
confidence: 49%
“…NSAIDs were usually administered in a regular timebased manner. 14,15 In our study, we found a significant reduction of diclofenac consumption (40%, p < 0.001) in patients with TAP block as diclofenac was administered every 8 h only if a mother reported moderate to severe pain (VAS > 4 cm). As Abdallah et al 23 suggested, patients with conditions that prohibit them from taking NSAIDs (allergy, peptic ulcer, abnormal platelets and renal impairment) might benefit from TAP block.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…O TAP ecoguiado em cesariana foi avaliado em 10 ECR 19---27 ; entre elas foi avaliada em cesariana com anestesia espinhal em oito ECR 19---23,25,27 ; deles, quatro 20,22,23,27 compararam TAP vs. morfina espinal (MIT), dois compararam contra TAP placebo, 19,21 um deles avaliou a adição de O estudo se descreve como aleatorizado? Sim = 1 ponto; Não = 0 ponto O método usado para produzir a sequência aleatorizada é descrito e apropriado?…”
Section: Resultsunclassified
“…Adicionou-se adrenalina em três 22,37,45 e clonidina em um. 25 Unicamente em duas compararam-se concentrações diferentes de AL.…”
Section: Drogas Volumes E Dosesunclassified